RABDOMIOLISIS - Wangko, Sunny (Jurnal Biomedik : JBM, 2013)
Abstract: Literally, rhabdomyolysis is the occurence of skeletal muscle destruction, resulting in massive liberation of muscle fiber constituents (electrolytes, myoglobin, creatine kinase, and other sarcoplasmic proteins) into the extracellular fluid and the blood circulation. The etiological spectrum of rhabdomyolysis is extensive, consisting of: physical factors such as trauma and compression, ischemia of skeletal muscle tissue, strenuous physical exercise, prolonged immobilization, high-voltage electrical injury, hyperthermia; and non-physical factors such as metabolic myopathy (genetic disorders), drugs and toxins, viral and bacterial infections, electrolyte and endocrin abnormalities, connective tissue disorders; and unknown causes. Although the causes of rhabdomyolysis vary extensively, the histopathological findings usually show a loss of cell nuclei and muscular striation with the absence of inflammatory cells. The pathophysiology of rhabdomyolysis includes changes in cellular metabolism, reperfusion injury, and the compartment syndrome. The degrees of rhabdomyolysis vary from a subclinical rise of creatinine kinase to an emergency condition with multiorgan failure. Classically, the clinical findings are muscular aches and swelling, as well as dysfunction, stiffness, numbness, weakness, and tea-colored urine. The most important laboratory examinations are serum creatinine kinase, besides serum and urine myoglobin. The life-threatening complications of rhabdomyolysis are hypovolemia, arrhythmia and cardiac arrest, acute kidney injury, and DIC. Its early diagnosis and prompt management are very important to the progress of the patient as well as to the effective control of rhabdomyolysis. Medical personnel, pharmacists, sport/gym instructors, and athletes have to be aware of the signs and symptoms of this rhabdomyolysis. Keywords: rhabdomyolysis, electrolytes, myoglobin, creatine kinase Abstrak: Rabdomiolisis adalah terjadinya destruksi serat otot rangka yang berakibat terlepasnya konstituen serat otot (elektrolit, mioglobin, kreatin kinase, dan protein sarkoplasma lainnya) ke dalam cairan ekstrasel dan sirkulasi. Penyebab rabdomiolisis multifaktorial, terdiri dari: faktor fisik, antara lain trauma dan kompresi, iskemia jaringan otot, latihan fisik berat, imobilisasi berkepanjangan, paparan listrik bertegangan tinggi, hipertermia; faktor non-fisik, antara lain miopati metabolik (genetik), obat-obatan dan toksin, infeksi virus dan mikroba, gangguan elektrolit dan endokrin, kelainan jaringan ikat; dan penyebab yang tidak diketahui. Walaupun penyebab rabdomiolisis sangat bervariasi, gambaran histologik yang ditemukan umumnya berupa hilangnya inti serat otot dan corak serat, tanpa disertai adanya sel-sel radang. Patofisiologi rabdomiolisis yaitu perubahan metabolisme sel, cedera reperfusi, dan sindroma kompartemen. Derajat rabdomiolisis dapat bervariasi dari peningkatan kreatin kinase subklinis sampai yang memerlukan penanganan darurat disertai kegagalan multiorgan. Gejala klinis klasik berupa nyeri, pembengkakan dan disfungsi otot, kaku, kesemutan, kelemahan, serta urin berwarna teh. Pemeriksaan penunjang utama yaitu kreatin kinase serum, serta miogobin urin dan serum. Komplikasi yang sangat mengancam kehidupan ialah hipovolemia, aritmia dan gagal jantung, gagal ginjal akut, serta DIC. Diagnosis dini dan penanganan segera sangat berperan dalam perlangsungan rabdomiolisis dan prognosis pasien. Tenaga medis, tenaga farmasi, instruktur olah raga dan gym perlu diwaspadai terhadap gejala rabdomiolisis. Kata kunci: rabdomiolisis, elektrolit, mioglobin, kreatin kinase